Transitioning from Subtyping to Precision Medicine in Parkinson's Disease: A Purpose‐Driven Approach - Marras, Connie; Fereshtehnejad, Seyed‐Mohammad; Berg, Daniela; Bohnen, Nicolaas I.; Dujardin, Kathy; Erro, Roberto; Espay, Alberto J.; Halliday, Glenda; Van Hilten, Jacobus J.; Hu, Michele T.; Jeon, Beomseok; Klein, Christine; et al. (Movement disorders, 2024)
The International Parkinson and Movement Disorder Society (MDS) created a task force (TF) to provide a critical overview of the Parkinson's disease (PD) subtyping field and develop a guidance on future research in PD subtypes. Based on a literature review, we previously concluded that PD subtyping requires an ultimate alignment with principles of precision medicine, and consequently novel approaches were needed to describe heterogeneity at the individual patient level. In this manuscript, we present a novel purpose‐driven framework for subtype research as a guidance to clinicians and researchers when proposing to develop, evaluate, or use PD subtypes. Using a formal consensus methodology, we determined that the key purposes of PD subtyping are: (1) to predict disease progression, for both the development of therapies (use in clinical trials) and prognosis counseling, (2) to predict response to treatments, and (3) to identify therapeutic targets for disease modification. For each purpose, we describe the desired product and the research required for its development. Given the current state of knowledge and data resources, we see purpose‐driven subtyping as a pragmatic and necessary step on the way to precision medicine. © 2024 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.